Characterization of Adipose‐derived Stem Cells from Breast Cancer Cell Transplanted Mice - Giang, Tran Thi Huong; Anh, Nguyen Van; Hiep, Nguyen Thi; Nhung, Nguyen Thi; Ngoc, Bui Van; Hanh, Nguyen Van (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 3DO - 10.25073/2588-1140/vnunst.5330, 2023)
Mesenchymal stem cells (MCSs) from adipose tissue are reported to have a pronounced impact on tumor growth or suppression. However, so far, how the cancer cells affect the stem cells in vivo conditions has not been clarified. In this study, we evaluated the impact of breast cancer cells on the characteristics of adipose-derived stem cells (ADSCs) under in vivo conditions. ADSCs were obtained from Balb/c mice in three consecutive weeks after transplantation with 1×10 6 MCF7 cells. The results showed that the amount of ADSCs per one gram fat reduced over time, but that reduction was not significantly different. In fact, isolated ADSCs presenting specific MSC surface markers increased at the second passage, compared to the time of isolation. Particularly, they were highly positive for CD90 (a MSC indicator) and negative for CD45 (a hematopoietic marker). Moreover, in in vitro culture, ADSCs were successfully differentiated into adipocytes, which were detected by Oil Red O staining. This present experiment gives initial assessments of ADSC characteristics; however, further investigations are necessary to fully evaluate the differences in stem cell potency and immunophenotype caused by cancer cell transplantation.